1-[3-(4-Chlorophenyl)isoquinolin-1-yl]-3,5-diphenyl-1H-pyrazole - Khan, F.N.; Manivel, P.; Krishnakumar, V.; Hathwar, V.R.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(30)H(20)ClN(3), is composed of a diaryl-substituted pyrazole ring connected to an aryl-substituted isoquinoline ring system with a dihedral angle of 65.1 (1)degrees between the pyrazole ring and the isoquinoline ring system. The 3-phenyl and 4-phenyl substitutents are twisted by 8.1 (1) and 43.0 (1)degrees, respectively, with respect to the pyrazole ring. The chlorophenyl ring and the isoquinoline ring system are twisted by 21.2 (1)degrees with respect to each other.